Haremlik - Vaka, Demetra, 1877-1946. (Piscataway, NJ)
xxv, 275 sayfa
Keywords: “Born as a Greek Ottoman in Istanbul, Demetra Vaka Brown (1877-1946) moved to America where she became a journalist and novelist, revisiting Turkey to write several books about the twilight of the Ottoman Empire and the emergence of the Turkish Republic. She based this, her first book, on experiences from 1901, when modernization had made inroads into Ottoman domestic life and the harem was becoming a thing of the past. Her reflections on life in the harem suggest the conflicted nature of her allegiances: Vaka is nostalgic for the Ottoman life that was rapidly disappearing, but she also enjoys the freedoms of a professional American woman“ -- Yayıncı.